FOOD DIVERSIFICATION TO IMPROVE THE NUTRITIONAL STATUS OF CHILDREN AGED 6-24 MONTHS THROUGH COLLABORATION BETWEEN HEALTH WORKERS AND THE COMMUNITY IN SUKAMAJU VILLAGE, TAMBELANG DISTRICT: FOOD DIVERSIFICATION TO IMPROVE THE NUTRITIONAL STATUS OF CHILDREN AGED 6-24 MONTHS THROUGH COLLABORATION BETWEEN HEALTH WORKERS AND THE COMMUNITY IN SUKAMAJU VILLAGE, TAMBELANG DISTRICT - Ananda Patuh Padaallah; Aprilina Sartika; Previarsi Rahayu; Nurul Imam (Community Service Journal of Indonesia, 2026)
Nutrition problems in children aged 6–24 months remain a public health challenge, especially during the period of complementary feeding. Lack of food variety, limited knowledge among mothers, and the suboptimal role of health workers are risk factors for nutrition problems. This community service activity aims to improve children's nutritional status through a food diversification program based on collaboration between health workers and the community in Sukamaju Village, Tambelang District. The methods used in this activity included identifying nutritional problems, providing education on complementary feeding based on local foods, training on menu diversification, health worker assistance, and evaluating the nutritional status of children aged 6–24 months. A total of 26 mothers and health workers were involved in this activity. The evaluation was conducted through weight measurements, knowledge assessments, and observations of complementary feeding practices. The results of the activity showed an increase in mothers' knowledge about diversifying complementary feeding, an increase in cadres' skills in nutrition education, and an increase in the variety of children's daily menus. This collaborative program effectively raised community awareness about the use of local foods as a source of nutrition for children. It was concluded that collaboration between cadres and the community through a participatory approach can improve the quality of complementary feeding.